Investor and Venture Fund Managers Remuneration Paid Mechanism Based on Principle-Agent Model - Shiue, Yih-Chearng; Lee, Ming-Chang; Lin , Pei-Jian; Huang, Yao-Wen (Asian Journal of Empirical Research, 2015)
In order to solve problems in investor and venture fund managers remuneration paid mechanism, the paper presents the asymmetric information games existing in construction mechanism through information economics viewpoints. The paper building investor and venture fund managers remuneration paid mechanism based on principal- agent theory, remuneration excitement and risk constraints. The results of this paper are: (1) Under the venture fund managers’ optimal efforts, investors willing to pay for agent fund profits’ optimal proportion (2) venture fund manager willing to inject capital amount. The main contribution of this paper is to examine the problems of principal-agent relationship between the principal and agent. The paper validates the model (1) Optimal contract model between investor and venture fund managers (2) Equilibrium contract model between investor and venture fund managers. Finally, the paper gives some suggestions and conclusion on how to enhance the Investor and venture fund managers remuneration paid mechanism.